2016
DOI: 10.1159/000443268
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic Hernia after Total Gastrectomy

Abstract: Intrathoracic hernias after total gastrectomy are rare. We report the case of a 78-year-old man who underwent total gastrectomy with antecolic Roux-Y reconstruction for residual gastric cancer. He had alcoholic liver cirrhosis and received radical laparoscopic proximal gastrectomy for gastric cancer 3 years ago. Early gastric cancer in the remnant stomach was found by routine upper gastrointestinal endoscopy. We initially performed endoscopic submucosal dissection, but the vertical margin was positive in a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In addition, three of four patients who underwent resection of the diaphragmatic crus did not undergo crus repair. Tashiro et al proposed that EHH could be caused by negative intrathoracic pressure, resection of the diaphragmatic crus, low BMI, and liver cirrhosis [ 8 ]. Ito et al suggested that crus incision without repair is associated with EHH after laparoscopic total gastrectomy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, three of four patients who underwent resection of the diaphragmatic crus did not undergo crus repair. Tashiro et al proposed that EHH could be caused by negative intrathoracic pressure, resection of the diaphragmatic crus, low BMI, and liver cirrhosis [ 8 ]. Ito et al suggested that crus incision without repair is associated with EHH after laparoscopic total gastrectomy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that LG could increase the risk of IH owing to less adhesion after surgery, compared with OG. 20 Especially, total gastrectomy with reconstruction using a long RY limb leads to dramatic weight loss postoperatively, and can result in a higher risk of IH after surgery. 21 IH after a laparoscopic RY limb procedure, such as transmesenteric and the Petersen hernia, are common postoperative complications because of the iatrogenically created structures.…”
Section: Discussionmentioning
confidence: 99%
“…In a Japanese study, of 8,938 patients with gastrectomy for gastric cancer, only 13 were diagnosed as having an internal hernia (0.19%) and only 1 was considered as having a hiatal hernia (0.01%) [2]. The proposed causes of hiatal hernia were negative intrathoracic pressure, resection of the diaphragmatic crus, and liver cirrhosis, which is because the esophageal hiatus, is commonly covered by the left lateral segment of the liver [12]. The cause of iatrogenic hiatal hernia is most likely blunt dissection of the hiatus during operation, which enlarges the hiatus[131415].…”
Section: Discussionmentioning
confidence: 99%